Implementasi Fatwa MUI tentang Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah pada Wisata Edukasi Kampung Tahu Desa Babalanlor Kecamatan Bojong Kabupaten Pekalongan - N. Syakirohtul Riskiyah; Amir Tajrid; Hasanudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to analyze the implementation of educational tourism in Pekalongan Regency. At the same time discussing the implementation of DSN-MUI fatwa No. 108 concerning the implementation of sharia-based tourism. The research method uses empirical juridical with a qualitative approach, this study was conducted in the tofu village tourism of Babalanlor Village, Pekalongan Regency, Central Java. The results of this study indicate that the implementation of educational tourism in Pekalongan Regency, especially in the tofu village of Babalanlor Village, Pekalongan Regency, is not a tour labeled as sharia tourism, but in its implementation there are some that have met sharia principles, this tour guide in providing guidance during visits uses clothing that is in accordance with Islamic law and wears a hijab for female guides, there is a prayer room that can be used to perform prayers in this tour, the food provided in this tour is also halal food and the guidelines for organizing tourism based on sharia principles contained in the DSN-MUI fatwa Number: 108 / DSN-MUI / X / 2016 have not been fully applied to the tofu village educational tour, but more sharia principles have been applied than have not been applied to this tour.